Improved x-ray detection and particle identification with avalanche photodiodes - Diepold, Marc (2015)
279765. F.D.A., L.M.P.F., A.L.G., C.M.B.M., and J.M.F.S. acknowledge support from FEDER and FCT in the frame of Project No. PTDC/FIS-NUC/0843/2012. C.M.B.M. acknowledges the support of FCT under Contract No. SFRH/BPD/76842/2011. F.D.A. acknowledges the support of FCT under Contract No. SFRH/BPD/74775/2010. A.A., K.K., and K.S. acknowledge support from SNF 200021L-138175. T.G., A.V., B.W., and M.A.A. acknowledge support of DFG_GR_3172/9-1. This research was supported in part by Fundacao para a Ciencia e a Tecnologia (FCT), Portugal, through Project Nos. PEstOE/FIS/UI0303/2011 and PTDC/FIS/117606/2010, financed by the European Community Fund FEDER through the COMPETE. P.A. and J.M. acknowledge the support of the FCT under Contract Nos. SFRH/BPD/92329/2013 and SFRH/BD/52332/2013.